Influence of Regional Pollution Outflow on Particle Number Concentration and Particle Size in Airshed of Guangzhou, South China - Hing Cho Cheung; Chengyu Nie; Mintao Huang; Tingting Yang; Hao Wang; Celine Siu Lan Lee; Chenglei Pei; Jun Zhao; Baoling Liang (Aerosol and Air Quality Research)
Abstract A measurement campaign of particle number concentration and size distribution was conducted at urban (SYSU) and suburban (Panyu) areas of Guangzhou, South China, during 16 January to 3 February 2020 before and during the Chinese New Year (CNY) holiday. Average particle number concentration (PNC) was 6.3 × 103 cm–3 and 9.7 × 103 cm–3, respectively, at urban and suburban sites, indicating the severe particulate matter (PM) pollution. The PNC in the region was influenced by monsoon and the land–sea breeze systems. During monsoon seasons, PM pollution occurred at a regional scale affecting the urban and suburban areas as indicated by the high PNC correlation (r value = 0.70), but the PNCs were lower than that during land-sea breeze period (with lower PNCM1/PNCLSB1 and PNCM2/PNCLSB2 ratios) due to the higher atmospheric dispersion. There is a strong local emission (mainly vehicular emissions) in both urban and suburban areas which was significantly lowered during the CNY period due to reduced human activities. The PM pollution was found to be significantly influenced by local emissions (dominated by Aitken mode particles) and new particle formation (NPF) process (dominated by nucleation mode particles). NPF event was found to be associated with a higher N10–25/H2SO4 proxy ratio during the low wind speed condition.